Hybrid model for software development: an integral comparison of DevOps automation tools - Poonam Narang; Pooja Mittal (Institute of Advanced Engineering and Science, 2022)
DevOps is a fine fusion of development and operations teams together to deliver more efficient, reliable and quality software. DevOps make use of alternative set of automation tools for different development stages of software. The research presented in th is paper analyses selective automation tools to provide comprehensive and comparative tabular analysis followed by graphical comparison according to latest Google Trends. Best performer tools out of these alternative tool sets are grouped together into int egrated tool chain (ITC) in order to escalate DevOps performance in future. A hybrid automated model for software development using these selective automation tools from the ITC is also proposed. This analytic comparison will prove to be a big utility for young researchers, students and software developers to be cognizant with DevOps automation cul ture. Study of other tools or enhancement of the proposed hybrid model could also be considered as a part of future research.